Characterization of Potential Virus Resistance Genes in Different Crops Through In-silico Approaches - Raza, Mehar Ali; Zaib, Rida; Khalid, Aimen; Afzal, Amna; Kanwal, Faheem; Azmat, Muhammad; Zafar, Imran; Shafiq, Shaista (Indus Journal of Bioscience Research, 2025)
Begomoviruses, particularly the cotton leaf curl virus (CLCuV), pose significant threats to global agriculture, especially cotton production. This study identified five resistance gene analogs (RGAs)—KT250635, KT886994, KT633945, KT885194, and KT633946—in Gossypium hirsutum and evaluated their potential against CLCuV using bioinformatics and molecular modeling approaches. Structural validation through Ramachandran plot analysis demonstrated that KT250635 and KT886994 had 92.6% residues in the most favored regions, while KT633945 and KT633946 exhibited slightly lower stereochemical reliability, requiring further refinement. GMQE scores ranged from 0.48 to 0.79, with KT250635 achieving a high residue quality score of 0.90. Functional annotation revealed significant homology, with KT250635 sharing 93.1% similarity with Sorghum bicolor and 97.1% with Gossypium raimondii, suggesting broad-spectrum resistance potential. Protein modeling and validation through I-TASSER and QMEAN-Z scores demonstrated structural stability, with KT250635 emerging as the most promising candidate. Phylogenetic analysis clustered KT250635 and KT886994 closely with resistance-related genes across diverse taxa, highlighting evolutionary conservation and functional significance. Additionally, KT633945 and KT885194 exhibited genetic similarity with peach and wild legumes, suggesting potential cross-species resistance traits. Bootstrap analysis with 1000 replicates ensured the robustness of the phylogenetic clustering. These findings provide a strong foundation for breeding CLCuV-resistant cotton varieties and underscore the importance of genetic insights in sustainable crop protection. These results contribute to understanding resistance mechanisms in cotton and may aid in the genetic improvement of susceptible varieties. Future studies should explore the functional role of these genes in resistance pathways and their potential applicability in other crop species to enhance resilience against viral pathogens.